PROSES ADVANCED dan IMPROVED BROWN COAL LIQUEFACTION PROCESSES (BCL): SEBUAH TINJAUAN TEKNIS DAN STUDI PERBANDINGAN - Lambok Hilarius Silalahi (Jurnal Energi dan Lingkungan (Enerlink), 2005)
The Proven Brown Coal Liquefaction Process (Proven BCL) has been successfully tried-out through a 50 t/d pilot plant using Yallourn coal from Australia. This process is lately developed and optimized into an Advanced Brown Coal Liquefaction Process with addition of several new technologies into Proven BCL.The next step is an Improved Brown Coal Liquefaction Process (Improved BCL) which puts more emphasizing in economical and environmental values and adjusted to the more specific characteristics of Banko Coal. This Improved BCL Process is also aiming to reduce the scale-up risks. A few new processes are left out of Improved BCL due to the unsuitability to the Banko Coal and disadvantages to the whole operation. This paper will evaluate the whole process characteristics of all three processes. The latest process, which probably has more feasible future in Indonesia, will be based on only the conceptual design.Kata kunci: Proven bcl, advanced bcl , improved bcl, steam reforming, coal gasification,Â slurry dewatering, coal liquefaction, inline hydro- treatment, solvent de-ashing.